2018
DOI: 10.21577/0103-5053.20180076
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Promoted Chemoselective Oxysulfonylation of Alkenes

Abstract: The ultrasound-assisted oxysulfonylation of different alkenes using sodium salts of organosulfinic acids under air atmosphere is described. The reaction is chemo-and regioselective and the corresponding β-keto-sulfones were obtained in good yields as major products. The use of ultrasound greatly accelerated the formation of products when compared to the conventional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In this work, the attempt to develop a non-expensive and environmentally friendly methodology for the synthesis of vinyl sulfones was based on a work previously described by our research group for the synthesis of β-keto-sulfones from an oxysulfonylation reaction catalyzed by ferric chloride. 26 Initially different parameters were evaluated using O-propargyl alkyne 1a (0.4 mmol) and benzenesulfinic acid sodium salt, 2a (0.8 mmol), as model-substrates. The first parameter evaluated was the appropriate catalyst to promote the reaction.…”
Section: Figure 1 Sulfones With Pharmacological Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the attempt to develop a non-expensive and environmentally friendly methodology for the synthesis of vinyl sulfones was based on a work previously described by our research group for the synthesis of β-keto-sulfones from an oxysulfonylation reaction catalyzed by ferric chloride. 26 Initially different parameters were evaluated using O-propargyl alkyne 1a (0.4 mmol) and benzenesulfinic acid sodium salt, 2a (0.8 mmol), as model-substrates. The first parameter evaluated was the appropriate catalyst to promote the reaction.…”
Section: Figure 1 Sulfones With Pharmacological Activitymentioning
confidence: 99%
“…7 In addition, some sulfones exhibited a broad spectrum of pharmacological activities such as antitumoral activity; 8 inhibitors of cruzain, 9 a cysteine protease that plays a crucial role in the life cycle of Trypanosoma cruzi, the etiologic agent of Chagas' disease; and inhibitors of falcipain-2, 10 a cysteine protease that plays an important role in the parasitic life-cycle (Figure 1). There are several methods described in the literature for the preparation of this class of compounds being the most common those based on decarboxylative methods 11 or sulfonylation reactions employing different classes of sulfur compounds such as sulfonylhydrazides, 12 sulfonyl halides, 13 sulfinamides, 14 sulfinates, 15 thiosulfonates, 16 thiols, 17 SO2, 18 and tosylhydrazones. 19 The use of salts of organosulfinic acids emerged as an alternative to the methods described above.…”
mentioning
confidence: 99%
“…FeCl 3 -catalyzed the aerobic oxysulfonylation of different alkenes using sodium salts under ultra-sonication irradiation in a short reaction time to provide a mixture of b-keto sulfones and b-hydroxy sulfones in good yields (Scheme 155). 220 Mostly, the 4substituted aromatic alkenes worked well with sodium aryl/ alkyl sulnates and the use of trans-stilbene led to a complex mixture. In the case of a-methylstyrene, b-hydroxysulfone was formed exclusively in a 90% yield.…”
Section: Synthesis Of Sulfones (R-mentioning
confidence: 99%
“…of FeCl 3 with (NH 4 ) 2 S 2 O 8 could also promote this difunctionalization reaction. 29 However, selectivity and yield was modest at best. Recently, Zhou's research team demonstrated an innovative protocol for highly enantioselective synthesis of b-hydroxysulfones from terminal alkynes and sodium sulnates via Fecatalyzed aerobic oxysulfonylation and consecutive Ru-catalyzed asymmetric transfer hydrogenation in an aqueous medium under mild conditions.…”
Section: Sodium Sulfinates As Sulfonylating Agentsmentioning
confidence: 99%